RESPON BERBAGAI AKTIVATOR DALAM PUPUK ORGANIK CAIR DARI LIMBAH BUAH DI PASAR DAN KONSENTRASINYA TERHADAP HASIL SELADA KROP - Eko H. A. Juwaningsih; Nova D. Lussy; Chatlynbi T. Br. Pandjaitan (Politeknik Pertanian Negeri Kupang, 2018)
The aim of the study is to obtain POC which is one of activator and concentrate to increase the growth of krop lettuce. This study used RAK with 2 handling factors was repeated 3 times. Factor 1 (A): activator, namely: A1 = EM4, A2 = JB3, A3 = EMOL, A4 = ISO and A5 = BK Water; factor 2 (B): POC concentration (B), namely: B1 = 5, B2 = 10, B3 = 15, B4 = 20 and B5 = 25 ml / l water. Then the variance of analyzed and if it is proven to be real, it will be completed with a BNJ Test of 5%. The results of the study: 1) The concentrate of POC which is able to give the best lettuce yield JB3 10 ml / l water (wet weight 289.82 g / plant and dry weight 11,100 g / plant). 2) The results of activator interactions and POC concentrations are able to give the best lettuce yield of JB3 10 ml / l water.